2015
DOI: 10.1149/2.0681506jes
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Aluminum-Doped LiNi0.5Co0.2Mn0.3O2: Electrochemical Behavior, Aging, Structural Transformations, and Thermal Characteristics

Abstract: This paper is dedicated to studies of the electrochemical behavior, the structural and thermal features of the Ni-rich LiNi 0.5 Co 0.2 Mn 0.3 O 2 undoped and Al-doped (∼0.01 at.%) materials for positive electrodes of lithium batteries. We have found that structural characteristics of these materials are quite similar from the crystallographic point of view. It was demonstrated that Al substitution in the doped LiNi 0.5 Co 0.2 Mn 0.3 O 2 is preferred at Ni sites over Co sites, and the thermodynamic preference f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
125
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 132 publications
(133 citation statements)
references
References 76 publications
7
125
0
1
Order By: Relevance
“…While small pores act as transport channels for ions to the bulk of the electrode, larger pores allow for easy mass transport of solvated ions [94,95]. [68,[96][97][98][99][100][101]. Dopants play various roles in the material.…”
Section: Porous Li-and Mn-rich High-energy-density Cathode Materialsmentioning
confidence: 99%
See 3 more Smart Citations
“…While small pores act as transport channels for ions to the bulk of the electrode, larger pores allow for easy mass transport of solvated ions [94,95]. [68,[96][97][98][99][100][101]. Dopants play various roles in the material.…”
Section: Porous Li-and Mn-rich High-energy-density Cathode Materialsmentioning
confidence: 99%
“…The materials under examination were LiNi0.6Co0.2Mn0.2O2 and LiNi0.54Zr0.04Co0.2Mn0.2O2, synthesized by a [68,[96][97][98][99][100][101]. Dopants play various roles in the material.…”
Section: Zirconium and Aluminum Doping Of Li[nixcoymnz]o2 Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…[3][4][5][6][7][8][9][10][11][12][13] In studies of LiNi 1/3 Co 1/3 Mn 1/3 O 2 (NCM333) cathodes, it was demonstrated 4-6 that they provided a capacity of 200 mAh/g in the voltage range of 2.5-4.6 V, or ∼155 mAh/g if the cutoff voltage is limited by 4.3 V.…”
mentioning
confidence: 99%